Chapter 30 Women's activist filmmaking against gendered violence in Pakistan - Imran, Rahat (Taylor & Francis, 2024)
With the heated discussion around #MeToo, journalistic reporting on domestic abuse, and the popularity of true crime documentaries, gendered media discourse around violence and harassment has never been more prominent. The Routledge Companion to Gender, Media and Violence is an outstanding reference source to the key topics, problems and debates in this important subject and is the first collection on media and violence to take a gendered, intersectional approach. Comprising over 50 chapters by a team of interdisciplinary and international contributors, the book is structured around the following parts: News Representing reality Gender-based violence online Feminist responses The media examples examined range from Australia to Zimbabwe and span print and online news, documentary film and television, podcasts, pornography, memoir, comedy, memes, influencer videos, and digital feminist protest. Types of violence considered include domestic abuse, ""honour""-based violence, sexual violence and harassment, female genital mutilation/cutting, child sexual abuse, transphobic violence, and the aftermath of conflict. Good practice is considered in relation to both responsible news reporting and pedagogy. The Routledge Companion to Gender, Media and Violence is essential reading for students and researchers in Gender Studies, Media Studies, Sociology, and Criminology.